2013
DOI: 10.1242/dev.096545
|View full text |Cite
|
Sign up to set email alerts
|

Whole population cell analysis of a landmark-rich mammalian epithelium reveals multiple elongation mechanisms

Abstract: Tissue elongation is a fundamental component of developing and regenerating systems. Although localised proliferation is an important mechanism for tissue elongation, potentially important contributions of other elongation mechanisms, specifically cell shape change, orientated cell division and cell rearrangement, are rarely considered or quantified, particularly in mammalian systems. Their quantification, together with proliferation, provides a rigorous framework for the analysis of elongation. The mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
0
48
1
Order By: Relevance
“…Unlike the previous analysis of proliferation in the secondary palate epithelium (Economou et al 2013), the proliferation index heat maps of palatal shelf mesenchyme showed a remarkably noisy and inconsistent pattern at all stages for both mutant and wild-type. Figure 3 shows illustrative examples for each stage, genotype and AP region.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Unlike the previous analysis of proliferation in the secondary palate epithelium (Economou et al 2013), the proliferation index heat maps of palatal shelf mesenchyme showed a remarkably noisy and inconsistent pattern at all stages for both mutant and wild-type. Figure 3 shows illustrative examples for each stage, genotype and AP region.…”
Section: Resultscontrasting
confidence: 85%
“…Growth itself is typically not isotropic expansion by proliferation, but involves directional increase. It has previously been shown in palate epithelium that a significant proportion of the AP growth in that tissue is not proliferation-based, but rather arises by cell shape change and cell rearrangement (Economou et al 2013). In the present paper, a preliminary study has been described, as methods for capturing the separate components of directional growth in three dimensions and in mesenchyme are still in development.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion and shaping of the Drosophila pupal notum and wing, and the mouse oral palate epithelium, are driven by the combined activity of cell division, rearrangement, shape changes, and cell extrusion (Economou et al, 2013;Guirao et al, 2015). Epithelial morphogenesis is a dynamic multiscale process that is the result of the coordination and integration of individual cell behaviors, including shape change, rearrangement, division, extrusion, and integration.…”
Section: Introductionmentioning
confidence: 99%
“…Developing tissues utilize different combinations of these cell behaviors in distinct biological contexts to drive morphogenesis. The expansion and shaping of the Drosophila pupal notum and wing, and the mouse oral palate epithelium, are driven by the combined activity of cell division, rearrangement, shape changes, and cell extrusion (Economou et al, 2013;Guirao et al, 2015). In contrast, salivary gland tube formation and germband extension in Drosophila embryos are driven by cell shape changes and cell rearrangements, with the latter process also including an additional small contribution from oriented cell divisions (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The first class focuses on the shape of cell outlines and their deformation [11, 12, 25, 27, 28]. For example, Blanchard et al define cell shape by fitting an ellipse to the cell outline (Figure 2A) [11].…”
Section: Connecting Cellular Deformation Processes To Global Tissumentioning
confidence: 99%